Reflections on foreign investment in natural recources of developing countries - J. P. Agarwal (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1976)
Both exploitation of Natural resources and activities of multinational corporations in developing countries have independently been subjects of vehement discussions surrounding the oil or in a wider sense raw material crisis emerging from the embargo of OPEC countries in 1973 and those on the New International Economic Order. This paper examines in this background the role of foreign private investments in the natural resources of developing countries in the light of their current policies. But compared with traditional definition of natural resources, they are conceived here more broadly. They include besides (1) minerals., energy sources, forests, etc., also (2) air, rivers, oceans, sun energy, climate and other environmental constituents which determine nature's absorptive capacity for industrial growth and pollution. Natural resources of the first group are called here non-renewable or exhaustive and those of the second group environmental resources. The dividing line between the two groups may, however, be in some cases very thin because all natural resources are subject to exhaustion, albeit to different degrees, and all of them are parts of environment. Nevertheless, a distinction between exhaustive and environmental resources is drawn in this paper in order to account for their varying importance for foreign private investments in developing countries and in this sense our definitions of the two groups of natural resources are purely subjective.
Keywords: 330